Anonyma vittnen - (O)förenlighet med lag och förväntad effekt - Khemir,Mimmi (2025)
In recent years, gang-related crime and its societal consequences have attracted considerable attention in both public debate and legislative policy in Sweden. The pace of legislative reform has accelerated, and several new substantive and procedural criminal law measures have been introduced with the aim of combating serious and organized crime. One of the most debated reforms is The Anonymous Witnesses in Criminal Cases Act (2024:1180) (sw. lagen (2024:1180) om anonyma vittnen i brottmål). The Act, which entered into force on January 1st 2025, allows courts, under certain conditions, to permit witnesses to give testimony anonymously during the preliminary investigation and at trail in criminal cases. The use of anonymous witness testimony has previously been alien to Swedish criminal procedure. During the legislative process, extensive criticism was directed at the reform by consolation bodies as well as by the Council on Legislation. This criticism primarily concerned the accused’s right to defense and the evidentiary effectiveness of anonymous witness testimony. The purpose of this thesis is to present the new Swedish regulation on anon-ymous witnesses and to place it in relation to the right to a fair trial under the Instrument of Government and the European Convention on Human rights. The thesis further analyses how anonymous witness testimony may be expected to be assessed within the framework of the Swedish principle of free evaluation of evidence. In addition, the case law of the European Court of Human Rights concerning anonymous and absent witnesses, as well as the views expressed by key consultation bodies prior to the enactment of the legislation, are examined. In the light of the limited Swedish case law in this area, the doctrinal analysis is supplemented by a survey conducted among judges in Swedish district courts. The overall conclusion is that the Act on Anonymous Witnesses in Criminal Proceedings constitutes a significant departure from the fundamental principles of Swedish criminal procedural law. While the regulation is, to some extent, designed in accordance with tie requirements of the European Conven-tion and the case law of the European court of Human rights, it emphasizes the need for proportionality and legal certainty. At the same time, the use of anonymous witness testimony requires considerable caution and is expected to be accorded limited evidentiary value unless supported by other evidence. The results of the survey indicate that the evidentiary value of an isolated anonymous witness statement is generally perceived as low, and that judges consider alternative measures to be more appropriate than anonymity in ensuring the availability of evidence. Taken together, this suggests that anonymous witnesses in criminal proceedings are likely to have a restrictive and cautions application in Swedish law.
Keywords: Vittnen; straffrätt